Wybrane zagadnienia zmian legislacyjnych w czasie pandemii - Wrześniewska-Wal, Iwona; Augustynowicz, Anna; Hajdukiewicz, Dariusz; Janiszewska, Lidia; Waszkiewicz, Michał; Zgliczyński, Wojciech (Wiedza Medyczna, 2021)
The aim of the article was to present selected problems of health policy in the context of legislative changes in health care on the example of activities related to the SARS-CoV-2 virus epidemic, as well as to show the scope and pace of changes and their assessment. The first group of issues covers the analysis of the provisions introduced regarding organizational changes in entities providing medical activities, which, from the beginning of the pandemic, changed the scope of inpatient care and developed teleporting activities. The second group consists of changes that overlapped with regulations counteracting SARS-CoV-2 virus infections in the scope of GDPR and medical documentation. The third is an analysis of legal provisions regulating in detail the rights and obligations of medical personnel and patients, which on the one hand modify the legal liability of persons providing services, and on the other, introduce restrictions on access to them.